2010
DOI: 10.1111/j.1537-2995.2010.02819.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel test for microparticles in platelet‐rich plasma and platelet concentrates using dynamic light scattering

Abstract: Correlation with flow cytometry and microscopy showed that ThromboLUX is well suited to measure PMP concentration and size distribution in PLT concentrate samples. In combination with noninvasive sampling, ThromboLUX could provide routine microparticle enumeration of PLT-containing samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…As previously shown by electron microscopy, 14 new techniques such as laser-induced nanotracking, 16,17 atomic force microscopy, 18,19 and dynamic light scattering [20][21][22] recently confirmed that the major part of MP counts falls below the detection threshold of sd-FCM. However, recent FCM innovations strive for an MP numeration closer to these sensitive techniques while giving supplemental information such as immuno-phenotype.…”
Section: Discussionmentioning
confidence: 76%
“…As previously shown by electron microscopy, 14 new techniques such as laser-induced nanotracking, 16,17 atomic force microscopy, 18,19 and dynamic light scattering [20][21][22] recently confirmed that the major part of MP counts falls below the detection threshold of sd-FCM. However, recent FCM innovations strive for an MP numeration closer to these sensitive techniques while giving supplemental information such as immuno-phenotype.…”
Section: Discussionmentioning
confidence: 76%
“…For example, it is expected that size distributions of polydisperse samples are biased toward small numbers of large particles [44,45], such as platelets and other contaminants, because such particles scatter light more efficiently than small vesicles. Therefore, DLS typically obtains a more than twofold increase in the median diameter of vesicles from plasma compared with other novel techniques [6,12,16,46,47]. We conclude that DLS requires careful data interpretation and may be a useful method provided that the shape of the size distribution is known.…”
Section: Dynamic Light Scatteringmentioning
confidence: 83%
“…The microparticles are gated in the forward versus side scatter dot plot. In flow cytometry, the concentration of microparticles is determined relative to a known concentration of fluorescently labeled microspheres with a size of 1,000 nm as previously described [20]. In apheresis platelets the concentration of microparticles calculated from the ThromboLUX score strongly correlated with the microparticle content determined by flow cytometry ( fig.…”
Section: Comparison Of Thrombolux Results With Flow Cytometrymentioning
confidence: 99%
“…Both platelet viability and the number of microparticles are very challenging to assess by microscopy. Microparticles are extremely difficult to capture due to their small diameter of about 200-400 nm and their quick movement in and out of focus [20]. Furthermore, microscopy scoring methods such as the modified Kunicki morphology score ignore potentially important characteristics of platelet concentrates such as microparticle content, microaggregates, and other unclassified particles [3].…”
Section: Comparison Of Thrombolux Results To Microscopymentioning
confidence: 99%